PERLINDUNGAN KONSUMEN TERHADAP PEMBATALAN TRANSAKSI SECARA SEPIHAK PADA MARKETPLACE MENURUT UNDANG - UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (KASUS: BAPAK SAYID TAHUN 2021) - Silvya Marwah (Jurnal Hukum Adigama, 2021)
In this day, it is easy to obtain goods and/or services as needs that must be met because several platforms provide for the sale of goods and/or services that are much needed by the people themselves. One example of the platform itself is a marketplace. Marketplace is a gathering place between business actors and consumers on a website. The problem in this research is the legal protection for consumers who experience cancellation of transactions unilaterally according to law number 8 of 1999 concerning consumer protection. The research method used is normative research. Based on the results of the research, business actors must provide compensation to consumers, because they have violated consumer rights which have been regulated in Article 4 of the Consumer Protection Law.